Pengaruh Kepemilikan Institusional, Kepemilikan Manajerial, dan Pertumbuhan Penjualan Terhadap Nilai Perusahaan - Muhammad Ben Hatta; Ratih Qadarti Anjilni (Jurnal Riset Akuntansi, 2025)
This study aims to determine the influence of Institutional Ownership, Managerial Ownership and Sales Growth. The population of this study is companies in the Non-Cyclicals Customer Sector sub-sector Food and Beverage on the Indonesia Stock Exchange during the period 2019-2023. The population in this study is 84 research companies, this study uses a data sample of 9 companies within a period of 5 years. Sampling was carried out using purposive sampling. This research is a qualitative research that uses classical assumption tests and multiple linear regression analysis. The data used in this study is secondary data in the form of financial statements. Data analysis used multiple regression analysis processed using the Econometric Views (EViews) program 12. The data analysis technique used in this study is panel data regression with a random effect model. The results of this study show that institutional ownership, managerial ownership and sales growth have a significant effect on the value of companies in the consumer non-cyclicals sub-sector food and beverage sector. Managerial ownership has a significant effect on company value while institutional ownership has no effect on company value, sales growth has no effect on company value in the consumer non-cyclicals sub-sector food and beverage sector.